The role of Dimensions of 0rganization Development in the Organization Commitment of Faculty Members of Physical Education of Universities of the Country - Morteza Nikoofar; Mehrdad Mazaheri (پژوهش‌های مدیریت عمومی, 2017)
Extended Abstract Employee commitment can have positive outcomes for the organization and preventing displacement, absenteeism and leaving the organization. A retirement plan should be drawn up to maintain and increase the organizational commitment of the staff. Therefore, it is necessary to investigate factors affecting organizational commitment. The purpose of this study was to Identification the role of Dimensions of organizational development in the organizational commitment of faculty of physical education in the country. The present research is of correlation and performed in Field method. The study of 215 people, including all members of the faculty of physical education across the country. Introduction The development and qualitative growth of the faculty members is one of the goals of today's universities, For this reason, Developing and implementing programs for the growth of these specialists is necessary, The development of faculty members includes activities that help them grow and Promoting Professional capabilities. Improve the development of faculty could have a positive impact on their organizational behaviors without hesitation. Organizational commitment of members can be one of these. Organizational commitment of employees is the positive and negative attitudes of individuals toward the organization. Organizational commitment has three dimensions that are: - Strong belief in accepting the goals of the organization - A lot of passion for more effort in the organization - The desire to continue membership in the organization. Gall (2015), showed a positive and significant correlation between organizational commitment and employee organizational development in their research at Preston University. Very little research has been done on this subject. It is necessary to do more research in this field . The present research wants to answer these questions: Is there a relationship between organizational development and its dimensions, and the degree of organizational commitment of the faculty members of the country's physical education colleges? Do dimensions of organizational development can predict the organizational commitment of the faculty members of the country's physical education colleges? Case study The purpose of this study was to Identification the role of Dimensions of organizational development in the organizational commitment of faculty of physical education in the country. Materials and methods The present research is of correlation and performed in Field method. The study of 215 people, including all members of the faculty of physical education across the country. The sample size has been calculated against 138 people, using the Cochrane formula and is selected by stratified random sampling. In this research, organizational development questionnaire (Jamshidi, 1388) and questionnaire of organizational commitment (Allen and Meyer, 1997), which validity by experts and reliability through Cronbach's alpha, respectively, 0.78 and 0.86 respectively. To analyze the data, descriptive statistics, statistical methods, Pearson correlation coefficient, and stepwise multiple regression analysis to single-sample t-test and Kolmogorov-Smirnov was used. Discussion and results The results showed that between organizational development and all its aspects, and organizational commitment of faculty members in the P<0.01 a direct and significant relationship exists. Multiple regression analysis showed that the dimensions of organizational development in the next step interpersonal communication, self-efficacy and leadership are able to significantly predict organizational commitment. Conclusion Organizational development and its various dimensions have features that Can change the expectations of faculty members of physical education and Allowing them to perform beyond the individual's interests and beyond what is expected and Also ultimately lead to a greater commitment to organizational goals. Therefore, it is suggested that University directors help to expand interpersonal, inter-group, and work-based communication, focusing on the impact of faculty members on the country's growth, and the use of organizational development plans as one of the factors contributing to growth and Development of organizations.